Faktor yang Memengaruhi Kepatuhan Wajib Pajak Orang Pribadi di Wilayah Tangerang - Myken Vanda Gishela; Rian Sumarta (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The aims of this study are to determine the factors that affecting the control of personal taxpayers’ attitudes regarding the implementation of tax education, tax knowledge, tax penalty, account representative’s services, tax amnesty, tax awareness, and the application of e-filing system. The object of this study was conducted on personal taxpayers registered in Tangerang tax office. The data were collected by questionnaire measured by likert scale. Purposive sampling sampling technique were applied to determine the samples in this study and the number of samples in this study consisted of 131 personal taxpayers that registered in Tangerang tax office. data analysis was performed by validity test, reliability test. The hyphotesis was tested using the coefficient analysis, coefficient of determination (adj R2), t and F test statictics. The results showed that the implementation of tax knowledge, tax penalty, and the application of e-filing system had a positive effect on individual taxpayers’ compliance that registed in Tangerang tax office. While, other independent variable do not have influence to tax compliance.